Let's complete the solution by following the steps you have outlined:
-
You decided to eliminate \(y\), and you are correct since \(-2.5y\) and \(2.5y\) are opposites.
-
Now, add the equations together:
\[ -9.5x - 2.5y + 7x + 2.5y = -4.3 + 0.8 \]
The \(y\) terms cancel out:
\[ (-9.5x + 7x) = -4.3 + 0.8 \]
\[ -2.5x = -3.5 \]
-
Now, solve for \(x\):
\[ x = \frac{-3.5}{-2.5} = \frac{3.5}{2.5} = 1.4 \]
-
Substitute \(x = 1.4\) into one of the original equations to solve for \(y\). Let's use the second equation:
\[ 7x + 2.5y = 0.8 \]
Substituting \(x = 1.4\):
\[ 7(1.4) + 2.5y = 0.8 \]
Calculate \(7(1.4)\):
\[ 9.8 + 2.5y = 0.8 \]
Now, isolate \(2.5y\):
\[ 2.5y = 0.8 - 9.8 \] \[ 2.5y = -9.0 \]
Now, solve for \(y\):
\[ y = \frac{-9.0}{2.5} = -3.6 \]
So, the solution to the system of equations is:
\[ \boxed{(1.4, -3.6)} \]